A conceptual framework for determining acceptance of Internet of Things (IoT) in higher education institutions of Pakistan - Shaikh, Humaiz; Khan, Mohammad Shadab; Ahmed Mahar, Zulfikar; Anwar, Maleeha; Raza, Ali; Shah, Asadullah (IEEE, 2019)
The IoT is the latest innovation and increasingly growing area to be implemented in all areas of life especially in higher education. This has created new excitement and challenges for academicians, this study will focus on IoT adoption and acceptance in higher educational institutes of Pakistan. The way IoT in learning environments supports educators can influence how we collaborate, communicate and operate. In this research, we focus on two aspects to investigate here. Firstly, how students are taught and; secondly, how educational institutes can bring in IoT to improve learning. This study explores the important aspect which influence the IoT acceptance and usage in an academic setting with in higher education institutes of Pakistan. Current study lays foundation for a comprehensive framework using trusted models of technology and scoial psychology like Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). This research proposes the network analysis approach to observe the users' behaviors towards different IoT applications usage in higher education. The considerations of key deliverable that have significant effect on the acceptance of IoT in higher education institutions of Pakistan and the in-depth analysis showed that few applications are being used heavily compared to all other applications.This study provides basis for developing countries to increase wider acceptance and use of IoT technologies in higher education to provide benefits for both students' and faculty members.